2019
DOI: 10.3390/molecules24203634
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Activities of Three Naphthoquinones against the Pine Wood Nematode, Bursaphelenchus xylophilus

Abstract: Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle, is a serious forest pest, causing enormous economic losses in pine trees in Korea, China, Japan, and countries in Western Europe. To prevent pine wilt disease (PWD), trunk injection with nematicide is performed in Korea. Although these nematicidal agents are quite efficient, the development of new nematicidal agents is needed to prevent pesticide resistance and reduce pest management costs. The aim of this study was to investigate nematicidal activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Naphthoquinones (NTQ) are naturally occurring compounds in several families of plants, such as Ancistrocladaceae, Avicenniaceae, Balsaminaceae, Bignoniaceae, Boraginaceae, Dioncophyllaceae, Droseraceae, Ebenaceae, Gentianaceae, Iridaceae, Juglandaceae, Plumbaginaceae, Scrophulariaceae, and Verbenaceae, algae, fungi, lichens, and animals, such as beetles and arachnids (Raspotnig et al, 2005 ; Pankewitz and Hilker, 2008 ; Babula et al, 2009 ). Among NTQ, juglone (5-hydroxynaphthalene-1,4-dione; JUG) and 1,4-naphthoquinone (naphthalene-1,4-dione; 1,4-NTQ) were shown to have nematicidal activity, among other properties (insecticide, herbicidal, anti-inflammatory, antibacterial, antifungal, anticancer, and cytotoxic properties) and thus are promising compounds to develop novel, natural, and effective nematicides, with lower environmental half-lives than traditional nematicides (Babula et al, 2009 ; Fischer et al, 2012 ; Esteves et al, 2017 ; Maleita et al, 2017 ; Wang et al, 2017 ; Cha et al, 2019 ; Laxmikant, 2019 ; Aminin and Polonik, 2020 ; Islam and Widhalm, 2020 ). However, knowledge on the effects of these compounds through RKN life cycle and their potential mode(s) of action are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Naphthoquinones (NTQ) are naturally occurring compounds in several families of plants, such as Ancistrocladaceae, Avicenniaceae, Balsaminaceae, Bignoniaceae, Boraginaceae, Dioncophyllaceae, Droseraceae, Ebenaceae, Gentianaceae, Iridaceae, Juglandaceae, Plumbaginaceae, Scrophulariaceae, and Verbenaceae, algae, fungi, lichens, and animals, such as beetles and arachnids (Raspotnig et al, 2005 ; Pankewitz and Hilker, 2008 ; Babula et al, 2009 ). Among NTQ, juglone (5-hydroxynaphthalene-1,4-dione; JUG) and 1,4-naphthoquinone (naphthalene-1,4-dione; 1,4-NTQ) were shown to have nematicidal activity, among other properties (insecticide, herbicidal, anti-inflammatory, antibacterial, antifungal, anticancer, and cytotoxic properties) and thus are promising compounds to develop novel, natural, and effective nematicides, with lower environmental half-lives than traditional nematicides (Babula et al, 2009 ; Fischer et al, 2012 ; Esteves et al, 2017 ; Maleita et al, 2017 ; Wang et al, 2017 ; Cha et al, 2019 ; Laxmikant, 2019 ; Aminin and Polonik, 2020 ; Islam and Widhalm, 2020 ). However, knowledge on the effects of these compounds through RKN life cycle and their potential mode(s) of action are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports on the modes of action of aromatic compounds against PWN. Cha et al [ 19 ] reported that naphthoquinones generate reactive oxygen species that cause oxidative stress in B. xylophilus . Rajasekharan et al [ 46 ] reported that 5-iodoindole, like abamectin, rigidly binds to the active sites of the GluCL receptor by molecular docking assay and suggested that this binding is crucial for maintaining the open pore structure of the GluCL complex.…”
Section: Resultsmentioning
confidence: 99%
“…Although PWN has not yet been reported to show resistance to abamectin, the alternative use of diverse agents is recommended to avoid the development of resistance and to achieve efficient control of PWN. In recent decades, as PWN control agents, the use of microorganism extracts, plant extracts, essential oils and volatiles has been suggested [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To manage this destructive disease, extensive efforts have been made to control PWN, chemical control being one of the most common approaches. However, the indiscriminate use of pesticides has not only posed environmental hazards, but also lead to the emergence of pesticide resistance in PWN [8]. Developing environmentally friendly pest control methods, such as RNAi or nematophagous fungal formulations, are necessary alternative solutions.…”
Section: Introductionmentioning
confidence: 99%